2014
DOI: 10.1186/s40694-014-0005-8
|View full text |Cite
|
Sign up to set email alerts
|

The capacity of Aspergillus niger to sense and respond to cell wall stress requires at least three transcription factors: RlmA, MsnA and CrzA

Abstract: BackgroundCell wall integrity, vesicle transport and protein secretion are key factors contributing to the vitality and productivity of filamentous fungal cell factories such as Aspergillus niger. In order to pioneer rational strain improvement programs, fundamental knowledge on the genetic basis of these processes is required. The aim of the present study was thus to unravel survival strategies of A. niger when challenged with compounds interfering directly or indirectly with its cell wall integrity: calcoflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…In most of the studies, A . niger (N402 or derivatives thereof) was cultivated under controlled submerged conditions in bioreactors and stressed either during germination [37, 43, 44] or during the exponential growth phase [45]. Interestingly, none of the secretion stress agents (DTT, tunicamycin) and none of the cell membrane or cell-wall stressors applied in these studies (caspofungin, fenpropimorph, FK506, aureobasidin A, natamycin) provoked an increase in anafp expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the studies, A . niger (N402 or derivatives thereof) was cultivated under controlled submerged conditions in bioreactors and stressed either during germination [37, 43, 44] or during the exponential growth phase [45]. Interestingly, none of the secretion stress agents (DTT, tunicamycin) and none of the cell membrane or cell-wall stressors applied in these studies (caspofungin, fenpropimorph, FK506, aureobasidin A, natamycin) provoked an increase in anafp expression.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, deletion of two transcription factors important for securing cell wall integrity of A . niger (RlmA, [44]; TupA, [47] did also not affect anafp expression. Likewise, confrontation of A .…”
Section: Resultsmentioning
confidence: 99%
“…In A. niger the requirement of RlmA for the induction of the α‐glucan synthase A gene ( agsA ) in response to Calcofluor white has been established (Damveld et al, 2005). Deletion of RlmA renders A. niger sensitive to Calcofluor white, and to a lesser extent also to other cell wall disturbing agents such as caspofungin (CA), aureobasidinA (AbaA), FK506 or fenpropimorph (FP), indicating that other remodelling mechanisms might exist (Fiedler et al, ). In the same study, transcription factor binding site enrichment analysis of differentially expressed genes in response to CA, AbaA, FK506 and FP was performed, which identified possible involvement of both RlmA and MsnA (homolog of Msn2/4 in S. cerevisiae ) transcription factors in counteracting CA‐induced cell wall stress.…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, transcription factor binding site enrichment analysis of differentially expressed genes in response to CA, AbaA, FK506 and FP was performed, which identified possible involvement of both RlmA and MsnA (homolog of Msn2/4 in S. cerevisiae ) transcription factors in counteracting CA‐induced cell wall stress. Indeed, deletion of the MsnA transcription factor, like deletion of the RlmA transcription factor, led to increased susceptibility towards CA (Fiedler et al, ). MsnA has been shown to be required for coping with several stress responses, including osmotic and oxidative stress (Han and Prade, ; Bose et al, ; Hong et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fiedler et al (2014) showed that A. niger senses and responds to cell wall stress with at least three transcription factors, RlmA, MsnA and CrzA 49 . Our transcriptomic data showed down-regulation of rlmA both in A. nidulans1542 and A. nidulansAbfA, indicating that these recombinant strains were regulated by cell wall stress caused by heterologous protein production 49 .…”
Section: Recombinant Strains Adapt Differently At Early and Late Timementioning
confidence: 72%